The Effect of Tuberculosis Self Management Education Based on Self Care Theory on Self Efficacy and Medication Adherence in Pulmonary Tuberculosis Patients - Ardianti Fauziah Rochmah; Chilyatiz Zahroh; Ima Nadatien (Indonesian Journal of Global Health Research, 2026)
Non-adherence to medication is still a major problem that has an impact on therapy failure, drug resistance, and increased morbidity and mortality. Multi Drug Resistant TB (MDR-TB) cases in Indonesia are ranked 3rd (7.4%) after India and Russia. Through an educational approach that empowers patients through Tuberculosis Self Management Education (TSME) based on Self Care Theory,  it is hoped that it will be able to increase self-efficacy and medication adherence to tuberculosis patients. This study aims to analyze the influence of Tuberculosis Self Management Education based  on Self Care Theory on self-efficacy and medication adherence in tuberculosis patients. Methods: The study used a quasi-experiment design with pretest–posttest with control group, population of 68 with a sample of 34 intervention group respondents and 34 control group respondents with accidental sampling technique. The independent variables are TSME based  on Self Care Theory, while the dependent variables include self-efficacy and medication adherence. The research instruments used were  TBSES-21 self-efficacy questionnaire  and MMAS-8 drug adherence. Data analysis used Paired t-test and Independent t-test. The study showed a significant improvement in self-efficacy and medication adherence in the intervention group after intervention compared to the control group (p = 0.000). Conclusion: There is an effect of TSME based on  Self Care Theory on self-efficacy and medication adherence in pulmonary tuberculosis patients. This intervention is recommended to be applied, especially TB patients and their families, nurses in nursing services to support the success of tuberculosis treatment.